Long-term care services of Department of Social Welfare Malaysia: demand projection / Nor Mariyah Abdul Ghafar, Mohd Zaki Awang Chek and Isma Liana Ismail - Abdul Ghafar, Nor Mariyah; Awang Chek, Mohd Zaki; Ismail, Isma Liana (Faculty of Administrative Science and Policy Studies, 2012)
The increasing number of older population might lead to an increase in the demand for the long-term care (LTC) services. Thus, the main objective of this study is to make projection of demand for the services required from the year 2015 to 2035 to reflect with the increase in the older population in Malaysia with focus on the services offered by the Department of Social Welfare (JKM) Malaysia. Ordinary least square technique is used to estimate the future number of the older people who might require the services. This study projected that the demand for each of the services provided by JKM will increase more than 100% from 2010 to 2035.